Flirtations : Rhetoric and Aesthetics This Side of Seduction - Hoffman-Schwartz, Daniel (Book collections on Project MUSE., 2015)
This volume addresses the under-theorised terrain of flirtation not as a subgenre of seduction but rather as a phenomenon in its own right. Drawing on the interdisciplinary history of scholarship on flirtation even as it re-approaches the question from a distinctly aesthetic and literary-theoretical point of view, the chapters here thus give an account of the practice of flirtation and of the figure of the flirt, taking up the act's relationship to issues of mimesis, poetic ambiguity, and aesthetic pleasure.